Harnessing urban biomass for energy and water production: an NSGA-II-based optimization approach - Parviz Heydari Nasab; Ata Chitsaz; Hiva Rashidzadeh; Alireza Rostamzadeh Khosroshahi (Energy Nexus)
In this research, were propose a multiple-system that includes gasification for syngas and heat production, a Brayton cycle for power generation, and the utilization of waste heat from the turbine. This waste heat is used in a two-effect absorption refrigeration system to produce cooling and in a 24-step, multi-stage flash (MSF) desalination process to produce fresh water. A certain amount of natural gas is added as an auxiliary fuel to increase the calorific value of the syngas produced in the gasifier. The main driver is biomass from municipal solid waste due to its renewable nature and availability in all cities. This system is thermodynamically modeled using the Engineering Equation Solver (EES) software. It provides integrated analysis and investigation of the effects of energy, exergy, and the Levelized Cost Of Energy (LCOE) and Levelized Cost Of Exergy (LCOEx) in multi-objective optimization of multiple-systems to achieve maximum efficiency and minimum cost. It has been validated with similar papers. Finally, using objective functions, the (LCOE) and exergy efficiency has been optimized using MATLAB software with the Non-dominated Sorting Genetic Algorithm (NSGA II) method. The results indicate that the system achieves a net power Output of 18.756 MW, a heating capacity of 1.75 MW, a cooling capacity of 17.77 MW, and a freshwater production rate of 47.7 kg/s. The energy efficiency is calculated to be 73.51 %, with an exergy efficiency of 26.31%. The (LCOE) and (LCOEx) are 0.062 $/kWh and 0.236 $/kWh, respectively. The system is designed with a useful life of 25 years. Optimization results reveal that the optimal range for the (LCOE) is between 0.0566 and 0.0592 $/kWh, while the exergy efficiency ranges between 26.21 % and 28.09 %.